2019
DOI: 10.3390/medicina55030075
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Predictors for Weight Correction Success of the First Paediatric Weight Correction Programme in Children’s Clinical University Hospital in Riga

Abstract: Background and objectives: The efficacy of a weight correction programme can be affected by such predictors as the number of contact hours, gender, age, baseline weight, parental weight status, psycho-emotional status, insulin resistance, and socioeconomic status. The aim of this current study was to evaluate the overall efficacy of the Weight Correction Programme at Children’s Clinical University Hospital, and explore the impact of the probable predictors. We evaluated the efficacy depending on gender, age, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
(57 reference statements)
1
5
1
Order By: Relevance
“…Furthermore, BMI-SDS changes were more likely to be maintained/decreased in patients who had a greater baseline WC. This is in contrast with the findings of previous studies, who reported larger initial waist circumference as a negative predictor of BMI-SDS reduction in lifestyle interventions for obesity treatment, suggesting the need for addressing more intensive interventions with obese children with specific abdominal fat distribution [ 41 , 42 ]. In agreement with systematic research on the predictors of weight loss and body weight loss maintenance in children with obesity, pre-existing physical activity did not have great impact on the success of the therapy [ 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, BMI-SDS changes were more likely to be maintained/decreased in patients who had a greater baseline WC. This is in contrast with the findings of previous studies, who reported larger initial waist circumference as a negative predictor of BMI-SDS reduction in lifestyle interventions for obesity treatment, suggesting the need for addressing more intensive interventions with obese children with specific abdominal fat distribution [ 41 , 42 ]. In agreement with systematic research on the predictors of weight loss and body weight loss maintenance in children with obesity, pre-existing physical activity did not have great impact on the success of the therapy [ 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The measurements of body mass and height were taken by a dietitian according to a widely applied methodology [35] using a calibrated weighing scale with an accuracy of ± 0.1 kg and a stadiometer with an accuracy of ± 0.5 cm. The BMI was calculated using the Quetelet's equation (body mass (kg)/height 2 (m 2 )), and the BMI percentile was assessed using the gender-and age-dependent growth reference cutoffs for children and adolescents suggested by the CDC [20] and related software [31,32], which were applied to indicate the specific percentile. A decreased BMI percentile was defined as a difference of more than one percentile between percentiles at the beginning of the program and after 1 year.…”
Section: Assessed Variablesmentioning
confidence: 99%
“…Family's place of residence (an open-ended question with the answer attributed to one of the following categories: village, city); − Parental marital status (a closed-ended question with the following possible answers: married, in a marriage-like relationship, separated, widowed, single; these were clustered afterwards into married/in a marriage-like relationship, separated/widowed/single); The measurements of body mass and height were taken by a dietitian according to a widely applied methodology [35] using a calibrated weighing scale with an accuracy of ± 0.1 kg and a stadiometer with an accuracy of ± 0.5 cm. The BMI was calculated using the Quetelet's equation (body mass (kg)/height 2 (m 2 )), and the BMI percentile was assessed using the gender-and age-dependent growth reference cutoffs for children and adolescents suggested by the CDC [20] and related software [31,32], which were applied to indicate the specific percentile. A decreased BMI percentile was defined as a difference of more than one percentile between percentiles at the beginning of the program and after 1 year.…”
mentioning
confidence: 99%
“…However, the need for further research into treatment motivation in children and adolescents with obesity was stressed [ 11 ]. The results for child and adolescent age and sex as predictors for successful weight loss have been contradictory [ 13 , 18 , 19 , 20 ]; one study found significantly greater treatment success in adolescent girls compared with treatment success in children and boys [ 21 ]. As an anthropometric parameter, a higher baseline weight status did not predict a greater BMI(-SDS) reduction within the scope of juvenile obesity therapies [ 14 , 19 , 20 ], despite a conflicting nature of the evidence [ 18 ].…”
Section: Introductionmentioning
confidence: 99%